Phlebotomus (Adlerius) simici NITZULESCU, 1931: first record in Austria and phylogenetic relationship with other Adlerius species - Kniha, Edwin; Dvořák, Vít; Milchram, Markus; Obwaller, Adelheid G; Köhsler, Martina; Poeppl, Wolfgang; Antoniou, Maria; Chaskopoulou, Alexandra; Paronyan, Lusine; Stefanovska, Jovana; Mooseder, Gerhard; Volf, Petr; et al. (Springer Science and Business Media LLC, 2021)
Phlebotomine sand flies are the principal vectors of Leishmania spp. (Kinetoplastida: Trypanosomatidae). Information on sand flies in Central Europe is scarce and, to date, in Austria, only Phlebotomus mascittii has been recorded. In 2018 and 2019, entomological surveys were conducted in Austria with the aim to further clarify sand fly distribution and species composition.